2014
DOI: 10.1158/1541-7786.mcr-13-0427
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing Associated with SWI/SNF Complex Loss during NSCLC Development

Abstract: The SWI/SNF chromatin-remodeling complex regulates gene expression and alters chromatin structures in an ATP-dependent manner. Recent sequencing efforts have shown mutations in BRG1 (SMARCA4), one of two mutually exclusive ATPase subunits in the complex, in a significant number of human lung tumor cell lines and primary non-small cell lung carcinoma (NSCLC) clinical specimens. To determine how BRG1 loss fuels tumor progression in NSCLC, molecular profiling was performed after restoration of BRG1 expression or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Recent sequencing efforts have shown silence of BRG1 in multiple primary NSCLC clinical specimens and human lung tumor cell lines. 31 In this study, BRG1 was confirmed to be significantly expressed at low levels in lung cancer tissues and cells. Furthermore, we validated that overexpression of BRG1 inhibited proliferation and metastasis of lung cancer cells and suppressed growth of xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 51%
“…Recent sequencing efforts have shown silence of BRG1 in multiple primary NSCLC clinical specimens and human lung tumor cell lines. 31 In this study, BRG1 was confirmed to be significantly expressed at low levels in lung cancer tissues and cells. Furthermore, we validated that overexpression of BRG1 inhibited proliferation and metastasis of lung cancer cells and suppressed growth of xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 51%
“…SMARCA4/BRG1 is an ATP-dependent catalytic subunit of the SWI/SNF chromatin remodelling complex, best known for its role in malignant rhabdoid tumors. Loss of SMARC4 has been reported in 5% to 20% of NSCLC, leading to epigenetic silencing of downstream genes, independent of DNA methylation (91,92). Interestingly, SMARCA4 deficient tumors are typically EGFR wild type and TTF-1 negative (93), suggesting that SMARCA4 loss could be a bone fide oncogenic driver event.…”
Section: Histone Modification and Chromatin Organizationmentioning
confidence: 99%
“…In addition to rare cancers such as clear cell RCC, glioblastoma multiforme and pancreatic cancers, which are significantly associated with inactivating mutations of SETD2 , a significant frequency of SETD2 alterations is observed in several more common tumors (Figure 1), including melanoma (11), bladder and lung cancer (cbioportal), which also exhibit alterations in other chromatin modifiers such as the SWI/SNF complex SMARCA4 ATP-ase subunit (12). …”
Section: Setd2 In Cancermentioning
confidence: 99%